1994
DOI: 10.1002/anxi.3070010404
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy of post‐traumatic stress disorder with a novel psychotropic

Abstract: This was a multicenter, randomized, double-blind, parallel trial conducted in outpatients in three countries. Following screening and placebo washout, patients received brofaromine (a combined MAO-A inhibitor/5-HT transport inhibitor) or placebo in a flexible dosing design. Based upon the CAPS, a standardized post-traumatic stress disorder (PTSD) interview, findings from a cohort involving both subchronic and chronic traumatic stress marginally favored brofaromine over placebo; however, not to a statistically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 11 publications
3
49
0
2
Order By: Relevance
“…In the efficacy analysis, 53% of patients were much or very much improved at treatment end point (P=.008 vs placebo), with 70% of the reduction in PTSD symptom severity on the CAPS-2 and IES achieved within the first 4 weeks of treatment ( Figure 2). The placebo response rate of 32% was comparable with what has been observed in previous multicenter PTSD clinical trials 23,24 as well as across most acute treatment studies of patients diagnosed as having affective or anxiety disorders.…”
Section: Commentsupporting
confidence: 82%
“…In the efficacy analysis, 53% of patients were much or very much improved at treatment end point (P=.008 vs placebo), with 70% of the reduction in PTSD symptom severity on the CAPS-2 and IES achieved within the first 4 weeks of treatment ( Figure 2). The placebo response rate of 32% was comparable with what has been observed in previous multicenter PTSD clinical trials 23,24 as well as across most acute treatment studies of patients diagnosed as having affective or anxiety disorders.…”
Section: Commentsupporting
confidence: 82%
“…In a US study, carried out predominantly among combat veterans, brofaromine failed to beat placebo on PTSD-specific measures [87], but showed good effect on a general global scale [88]. In the European study, Katz et al [89] reported a tendency for brofaromine to be more effective than placebo among those with the more chronic form of PTSD (i.e. lasting longer than 1 year), and on a global scale, the drug was statistically superior to placebo.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…[69] Post-travmatik stres bozukluğu (PTSB) hastalarında psikofarmakolojik tedaviye yanıtın %17 ile %68 arasında olduğu, öte yandan aynı hastalarda plasebo kullanımı sonrası yanıtın ise %28 ile %62 arasında olduğu bildirilmiş-tir. [70][71][72] Birçok çalışmada PTSB hastalarında tıbbi tedavi ile plasebo arasında fark olmadığı şeklinde veriler elde edilmiştir. [70][71][72][73][74] PTSB hastalarında plaseboya yanıtın yüksek olması ve PTSB'nin oluşumunda endojen opioidlerin rol oynaması, plasebo yanıtının oluşmasında endojen opioidlerinin etkisi olduğunu gündeme getirmiştir.…”
Section: Plasebo Etkisinde Endojen Opioidlerin Yeriunclassified
“…[70][71][72] Birçok çalışmada PTSB hastalarında tıbbi tedavi ile plasebo arasında fark olmadığı şeklinde veriler elde edilmiştir. [70][71][72][73][74] PTSB hastalarında plaseboya yanıtın yüksek olması ve PTSB'nin oluşumunda endojen opioidlerin rol oynaması, plasebo yanıtının oluşmasında endojen opioidlerinin etkisi olduğunu gündeme getirmiştir. [75] PTSB hastalarına ekzojen opioid verildiğinde içe çekilme ve aşırı uyarılmışlık belirtilerinde iyileşme olması, plasebonun da özellikle bu belirtilere endojen opioid sistemi üzerinden etkili olacağı-nı düşündürmektedir.…”
Section: Plasebo Etkisinde Endojen Opioidlerin Yeriunclassified